2007
DOI: 10.1016/j.freeradbiomed.2007.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Burn and smoke inhalation injury in sheep depletes vitamin E: Kinetic studies using deuterated tocopherols

Abstract: To test the hypothesis that burn and smoke injury will deplete tissue α-tocopherol and cause its faster plasma disappearance, deuterium-labeled vitamin E was administered to sheep exposed to both surface skin burn and smoke insufflation that causes injury similar to human victims of fire accidents. Two different protocols were used: 1) deuterated vitamin E was administered orally with food at 0 time (just prior to injury), or 2) the labeled vitamin E was administered orally with food the day prior to injury. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…We have previously published the sheep plasma aT levels and their response to injury [39]. In our present study, the plasma aT and gT levels did not change dramatically.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…We have previously published the sheep plasma aT levels and their response to injury [39]. In our present study, the plasma aT and gT levels did not change dramatically.…”
Section: Discussionsupporting
confidence: 55%
“…There is a report to show aT levels in bronchoalveolar lavage (BAL), the aT levels in BAL was 0.3 μM [42]. However, the lung aT concentration (5.8±0.4 nmol/g) in sheep was lower than human and swine lung [39], and as we showed previously, burn and smoke inhalation injury further reduced aT concentration in lung tissue [43]. In our present study, there were no significant differences in aT concentration in lung tissue; however, burn and smoke inhalation injury significantly reduced the gT concentration in lung tissue (Fig 2).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, isoniazid should not be dismissed as a possible cause in the event of rapid development of peripheral neuropathy with predominant motor symptoms after starting antituberculosis drugs, even in the absence of predisposing factors. It has been reported that smoking induces vitamin deficiency [2,3] but our patient had no history of smoking. The only possible explanation of this onset was his low BMI.…”
Section: Discussionmentioning
confidence: 68%
“…20 Data reported by Cetinkale et al 21 demonstrated that in addition to loss of plasma antioxidants like vitamin E and sulphydryl groups in patients with burns, vitamin C diminished early post-burn. Recently, Traber et al 22 suggested that a-tocopherol should be administered to burn patients to prevent vitamin E depletion and to protect against oxidative stress from burn injury. While vitamin E effectively scavenges free radicals within the cells, vitamin C would serve to scavenge free radicals within the extracellular space.…”
Section: Discussionmentioning
confidence: 99%